ADDICTIVE AND PSYCHOLOGICAL FACTORS IN A SAMPLE OF PATHOLOGICAL GAMBLERS - Llinares Pellicer, Maria Consuelo; Santos Diez, Patxi; Camacho Ferrer, Inma; Albiach Catalá, Carmen; Palau Muñoz, Carmen (Anales de Psicología / Annals of Psychology, 2003)
Objectives: The aim of the present work is to study the following variable factors: severity of pathological gambling, stage of change, anxiety and depression, and drug use, abuse or dependency. This work is also intended to study the existing relation among the variables stage of change, age and sex, and the remaining ones. Material and Methods: Data has been obtained from a clinical interview, SOGS, BDI, STAI, and CBA. The sample consists of 158 subjets (140 males and 18 females) all being addicted to gambling. Results: Results shows high severity on pathological gambling, high levels of both trait anxiety and state anxiety, as well as dysphoric mood. ½ of the sample subjects are in a contemplative state. Almost ½ of them show signs of gambling associated alcohol consumption. Conclusions: In our opinion, subjects with alcohol consumption associated problems require a specific kind of therapy. Subjects in a pre-contemplative stage have lower depression levels due to lack of concern and negation of the problem. Although subjects under treatment also show lower depression levels, in their case it is due to perceived self-efficiency following therapy instructions.